Ammonia Production as Alternative Energy for the Baltic Sea Region - Prause Gunnar; Olaniyi Eunice O; Gerstlberger Wolfgang (MDPI, 2025)
One of the consequences of the conflict in Ukraine relates to the growing shortfall in global ammonia production. There are additional negative global impacts on the availability of fertilizers and prices of ammonia (NH3). The shortage in ammonia production does not only influence the agroindustry but also the global shipping industry, as ammonia is positioned as a promising zero-carbon fuel and as a storage and transport medium for hydrogen. There are plans underway to start ammonia production in Estonia to minimize the consequences of the import stop of Russian ammonia in the context of the Ukrainian crisis. This study investigated the Baltic Sea Region (BSR) ammonia market and analyzed the economic implications of building an ammonia plant within the BSR. Using fuzzy real options models as the conceptual framework, together with secondary data analysis, case studies and expert interviews, the authors chart possible courses for the construction of ammonia production facilities within the region. Based on the case of the NH3 production plant, as well as the underlying distribution system, the study provides new economic perspectives for lower carbonization for the shipping industry, an attempt at creating a model for other European regions toward climate change mitigation.